2014
DOI: 10.1159/000363145
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity between Post-Traumatic Stress Disorder and Borderline Personality Disorder: A Review

Abstract: Background: Traditionally, the presence of post-traumatic stress disorder (PTSD) in subjects diagnosed with borderline personality disorder (BPD) has been the object of scant empirical research. The clarification of issues related to the different areas of study for this comorbidity is not only significant from a theoretical point of view but also relevant for clinical practice. The aim of this review is to describe the main theoretical findings and research conclusions about the comorbidity between PTSD and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 78 publications
(111 reference statements)
3
50
0
1
Order By: Relevance
“…For example, a chaotic family environment, independent of the experience of specific trauma events, may confer risk for the development of PTSD and/or AUD. Consistent with this perspective, a growing body of research indicates that an unstable home environment that is characterized by abuse, particularly sexual abuse, is relatively prevalent among women diagnosed with borderline personality disorder (BPD;Fr ıas & Palma, 2015). Other work suggests that women with BPD and/or related traits (i.e., affective instability) are related to alcohol misuse (Skodol et al, 2002;Trull, Sher, Minks-Brown, Durbin, & Burr, 2000).…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a chaotic family environment, independent of the experience of specific trauma events, may confer risk for the development of PTSD and/or AUD. Consistent with this perspective, a growing body of research indicates that an unstable home environment that is characterized by abuse, particularly sexual abuse, is relatively prevalent among women diagnosed with borderline personality disorder (BPD;Fr ıas & Palma, 2015). Other work suggests that women with BPD and/or related traits (i.e., affective instability) are related to alcohol misuse (Skodol et al, 2002;Trull, Sher, Minks-Brown, Durbin, & Burr, 2000).…”
Section: Sample Selectionmentioning
confidence: 99%
“…For instance, as highlighted above, recent research has begun to recognize the role of emotion dysregulation in PTSD-AUD comorbidity. From a broad perspective, difficulties in emotion regulation have been linked to a variety of adverse outcomes, including substance use (Sher & Grekin, 2007), PTSD (Ehring & Quack, 2010), mood/anxiety disorders (Campbell-Sills & Barlow, 2007), and BPD (Fr ıas & Palma, 2015). Women tend to report greater use of adaptive/maladaptive emotion regulation strategies in response to distress (Nolen-Hoeksema, 2012) and difficulty with goal-directed behavior when experiencing intense emotions (Tripp, McDevitt-Murphy, Avery, & Bracken, 2015).…”
Section: Identification Of Novel Mechanismsmentioning
confidence: 99%
“…In spite of these noteworthy findings, a more ecological approach to the specificity of EMSs is needed for BPD patients, which take into account their great comorbidity or categorical psychopathology. Concretely, epidemiological studies have found that BPD samples showed lifetime prevalence rates of up to 75% for eating disorders (ED), posttraumatic stress disorder (PTSD), major depression (MD), and substance use disorders (SUD; Frías & Palma, 2015;Kienast, Stoffers, Bermpohl, & Lieb, 2014;Köhling, Ehrenthal, Levy, Schauenburg, & Dinger, 2015;Zanarini, Reichman, Frankenburg, Reich, & Fitzmaurice, 2010). The need to address this issue is also justified by the fact that these comorbid disorders have been associated with specific EMSs when assessed alone (Ahmadian, Mirzaee, Omidbeygi, Holsboer-Trachsler, & Brand, 2015;Cockram, Drummond, & Lee, 2010;Pugh, 2015;Shorey, Stuart, & Anderson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…BPD is thus frequently comorbid with posttraumatic stress disorder (PTSD), with the diagnostic overlap reported to be between 33% and 79% (Frías and Palma, 2015). Individuals with PTSD and co-occurring BPD have more severe PTSD symptoms than those with PTSD and other comorbid disorders (Bolton et al, 2006), leading to greater impairment, a worse prognosis, and higher healthcare utilization (Connor et al, 2002; Frías and Palma, 2015). …”
Section: Introductionmentioning
confidence: 99%